ANALYSIS OF PHRASEOLOGICAL UNITS DENOTING TIME UNITS IN ENGLISH AND UZBEK (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates phraseological units denoting time in English and Uzbek languages from comparative, semantic, and linguocultural perspectives. Time-related phraseological expressions occupy a significant place in both languages because they reflect national worldview, cultural values, traditions, and historical experiences. The study aims to identify the structural and semantic peculiarities of phraseological units connected with time concepts in English and Uzbek, as well as to determine their similarities and differences. The research applies comparative, descriptive, and contextual analysis methods. The findings reveal that although both languages employ phraseological units to express temporal concepts metaphorically, cultural and social factors strongly influence their meanings and usage. English phraseological units tend to emphasize punctuality, efficiency, and productivity, whereas Uzbek expressions often reflect patience, wisdom, and collective social experience. The article contributes to comparative phraseology and intercultural linguistics by demonstrating how temporal concepts are represented differently in English and Uzbek phraseological systems.